IMPACT DE L’IMPLANTATION DES AGENCES DE TRANSPORT SUR LES TRANSACTIONS ECONOMIQUES DANS LA VILLE D’ISIRO : « Cas de Dissa Express et Dieu Merci » - Ignace, KWANDELEMAMA TIBINDE; Castro, MBULA ABDI; Augustin, TAMA KUMBAKO; Aminata, NGALULA TSHIPAMBA (IJRDO - Journal of Business Management, 2021)
This article focuses on the "impact of the establishment of transport agencies on economic transactions in the city of Isiro". It aims on the one hand to identify the impact of the location of transport agencies on economic transactions in the city of Isiro; and on the other hand to identify the agency that best corresponds to the expectations of economic operators in the city of Isiro in the Province of Haut-Uélé, Democratic Republic of Congo.The results showed that two factors influence the location of transport agencies in the town of Isiro. The first is the benefits offered by these agencies and the second is the benefits received by the economic operators, as shown by the Chi-square test on these variables above. Regarding the satisfaction of the economic operators by the transport agencies, we found that 54% or 27 economic operators prefer the transport services of Dissa Express and only 10% of them prefer that of Dieu Merci. But also a significant proportion, 36% are indifferent. In addition, it was found that 88% of the 100% of our respondents said that the establishment of these agencies had a positive impact on their activities against 4% of negative impact and 8% of no impact. Also, 100% of the economic operators interviewed, 54% prefer the transport services of Dissa Express and only 10% prefer the transport services of Dieu Merci, 36% are indifferent. The choice of Dissa Express by the respondents is justified by its speed, reliability, good packaging of goods and others in economic transactions and the number of places it frequents unlike its competitor.